2016
DOI: 10.3109/00952990.2015.1133633
|View full text |Cite
|
Sign up to set email alerts
|

Drinking motives mediate emotion regulation difficulties and problem drinking in college students

Abstract: The current results offer direction for potentially modifying brief alcohol interventions in efforts to reduce students' engagement in problem drinking behaviors. For example, interventions might incorporate information on the risks of using alcohol as a means of emotion regulation and offer alternative emotion regulation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…On the other hand, confirming the core hypothesis of the current study, however, results showed that daily stress had not only the direct effect on impaired control, but also indirectly affected on it via emotion dysregulation and drinking motives in serial. Consistent with recent studies (Aurora & Klanecky, 2016;Messman-Moore & Ward, 2014), these results showed that emotion dysregulation can be precursor to drinking motives.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, confirming the core hypothesis of the current study, however, results showed that daily stress had not only the direct effect on impaired control, but also indirectly affected on it via emotion dysregulation and drinking motives in serial. Consistent with recent studies (Aurora & Klanecky, 2016;Messman-Moore & Ward, 2014), these results showed that emotion dysregulation can be precursor to drinking motives.…”
Section: Discussionsupporting
confidence: 92%
“…Second, this study used self-report questionnaires, which their reliability could be lowered due to the respondents' social desirability. Especially in the case of the DERS, there may be an enormous difference between the respondents' perception of emotional regulation ability and their actual ability (Aurora & Klanecky, 2016). Finally, considering findings that the self-medication hypothesis was supported in cross-sectional than in prospective analyses (Read, Merrill, Griffin, Bachrach, & Khan, 2014), it needs to confirm whether the present results can also be replicated in the longitudinal study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Further, because depressed students who drank to cope did not necessarily drink heavily, there appears to be a need to investigate other factors influencing risk outcomes beyond intoxification itself. Further, the significant direct link between drinking to cope and alcohol problems in both samples points to the need for skills training for emerging adults who rely on drinking to cope and may lack the emotional regulation or volitional control known to protect them from alcohol-related harm, irrespective of drinking levels (Aurora & Klanecky, 2016). For example, college students who drink to cope are shown to use protective behavioral strategies that are less effective in reducing alcohol-related consequences (Patrick, Lee, & Larimer, 2011) such as those aimed at limiting consumption as opposed to more effective strategies for reducing serious harm (e.g., use designated driver) or avoiding high-risk situations (e.g., avoid drinking games) (Napper, Kenney, Lac, Lewis, & LaBrie, 2014; Pearson, Kite, & Henson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a study with 200 American college students, the aim was to investigate if drinking motives (conceptualized in the four-dimension model: drinking to cope, drinking to enhance emotional experience, drinking for social reasons and drinking to conform) (Cooper, 1994) mediated the link between emotion regulation deficits and problem drinking (Aurora & Klanecky, 2016). The results showed that drinking to cope motives fully mediated the emotion regulation/problem drinking relationship and enhancement motives partially mediated the relationship.…”
Section: The Role Of Emotion In Substance Use Disordermentioning
confidence: 99%